Changes in the prevalence of HBV infection in pregnant women in Turkey between 1995 and 2015: a 20-year evaluation - Furuncuoglu, Yavuz; Bolukbas, F. Fusun; Bolukbas, Cengiz; TORUN, PERİHAN; TORUN, PERİHAN; Ozturk, Recep (My University, 2016)
Objective To determine changes in hepatitis B virus (HBV) prevalence across three different time periods in pregnant women.